Visual Inspection with Acetic Acid (VIA) in cervical cancer screening in low resource settings (Bangladesh Journal of Medical Science, 2014)
Objective: To evaluate the feasibility and validity of visual inspection of the cervix with acetic acid (VIA) for screening cervical intraepithelial neoplasia. Materials and Methods: In this study, 942 women recruited from gynecology outpatient clinic, were screened using the Papanicolaou (PAP) smear, and VIA. The sensitivity and specificity of both the screening methods were analyzed. Results: VIA was positive in 29.3%. The sensitivity of VIA (74.16%) was much higher than that of the Pap smear (47.83%). The specificity of VIA (50.00%) was lower than that of the Pap smear (74.16%), resulting in high false-positive rates for VIA. Conclusion: Visual inspection of the cervix with acetic acid is sensitive for ecto-cervical lesions. The advantage of the VIA method lies in its easy technique, low cost and high sensitivity which are important factors for determining the efficacy of any screening program in developing countries. DOI: http://dx.doi.org/10.3329/bjms.v13i4.15019 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.454-459